DEVELOPMENT OF INTEGRATED INTERSTATE SYSTEM OF INFORMATION SUPPORT OF CUSTOMS AUDIT - VALENTINA Bereziuk (Учёт. Анализ. Аудит)
This article examines the formation of an integrated information management system of the interstate customs audit within the Eurasian Economic Union. It systematizes the reasons of the problems related to foreign trade activities and customs in Kazakhstan and highlights the principles of creation and operation of an integrated information management system for customs audit. The performance of the customs audit authorities largely depends on relevance, completeness and reliability of the information they use. An effective system of customs control and audit should provide the objective and reliable information on the use of the EAEC resources in accordance with the principles of legality, efficiency and effectiveness of the public authorities’ activity.The problems of information support of customs audit stated in the article can be solved by means of establishing the integrated interstate information and economic environment.